ANALISIS SISTEM MERIT DALAM REKRUTMEN APARATUR SIPIL NEGARA (ASN) TAHUN 2024 DI KABUPATEN MANOKWARI: Bahasa Indonesia - Virdha Melinda Amalia; Faradina Selsa Putri (Jurnal Kebijakan Pemerintahan, 2025)
Abstract The implementation of the merit system in the recruitment of civil servants and PPPK in Manokwari Regency is marked by the Special Autonomy Affirmative Action Policy of Manokwari Regent Regulation Number 105 of 2024 regarding formation provisions for Indigenous Papuans (OAP) with a quota of 80% and non-OAP 20%. This provision has the potential to sacrifice the principles of open competition and qualifications mandated by the merit system, which could lead to a decline in selection standards and inappropriate employee placements. Using a qualitative case study method with a literature review approach, this study analyzes Manokwari Regent Regulation No. 105 of 2024 and related literature to identify implementation challenges. The results of the study show that the 80:20 OAP and non-OAP formation policy creates a fundamental dilemma where, on the one hand, it protects OAP representation in the bureaucracy, but on the other hand, it risks lowering the competency standards of ASN, creating an “internal quality gap,” and does not solve the root cause of the low competitiveness of OAP human resources. Therefore, this study suggests the need for policy evaluation, improvement of the quality of education and training for OAP, revision of quota proportions, and increased transparency and accountability to ensure the quality and equity of human resources in the implementation of a good merit system in Manokwari Regency. Keywords: Merit system, ASN recruitment, Special Autonomy, Affirmation